2017
DOI: 10.3892/ol.2017.7281
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear expression of claudin‑3 in human colorectal adenocarcinoma cell lines and tissues

Abstract: Abstract.Claudins are members of a large family of transmembrane proteins, which are essential for the formation of tight junctions and have a significant effect on the biological behavior of tumor progression. Previous studies have demonstrated that several claudins show aberrant expression patterns in numerous types of cancer. The present study investigated the expression and localization of claudin-3 and claudin-7 in human colorectal adenocarcinoma cell lines and tissues. The protein expression levels of cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 63 publications
2
13
0
2
Order By: Relevance
“…Its delocalization into the nucleus was also observed in human osteosarcoma cells [81] and follicular thyroid carcinoma cells [82]. Moreover, claudin-2 was observed in the nucleus in human lung adenocarcinoma cells [83], and claudin-3 was reported to be present in nuclei in breast cancer cell lines [84] and human colorectal cancer [85]. Changes in claudin-4 location in endometrial cancer cells were also observed [86].…”
Section: Localization Of Claudins In Cellsmentioning
confidence: 74%
“…Its delocalization into the nucleus was also observed in human osteosarcoma cells [81] and follicular thyroid carcinoma cells [82]. Moreover, claudin-2 was observed in the nucleus in human lung adenocarcinoma cells [83], and claudin-3 was reported to be present in nuclei in breast cancer cell lines [84] and human colorectal cancer [85]. Changes in claudin-4 location in endometrial cancer cells were also observed [86].…”
Section: Localization Of Claudins In Cellsmentioning
confidence: 74%
“…Claudin family proteins consisting of at least 24 members are essential for the formation of TJs and have a significant effect on the biological behavior of tumor progression. Previous studies have demonstrated the several claudin (claudin-1 [62, 63], claudin-3 [64, 65], claudin-4 [64], claudin-7 [65]) aberrant expression patterns in colorectal cancer. Among them, claudin-1 and claudin-2 overexpression are identified in the present dataset.…”
Section: Resultsmentioning
confidence: 99%
“…Tokuhara и соавт . [14] [13] . Представленные в литературе данные позволяют высказать предположение о том, что ядерная экспрессия клаудина-3 может быть ассоциирована со степенью злокачественности и метастатическим потенциалом опухоли .…”
Section: Fig 3 Abnormal Nuclear Claudin-3 Expression In Gastric Canunclassified